2021
DOI: 10.4081/ejh.2021.3255
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Williams syndrome transcription factor (WSTF) suppresses glioblastoma cell growth and invasion by inhibiting PI3K/AKT signal pathway

Abstract: Williams syndrome transcription factor (WSTF) participates in diverse cellular processes, including tumor cell proliferation and migration. However, the function of WSTF in glioblastoma (GBM) remains unknown. Data from the Gene Expression Profiling Interactive Analysis (GEPIA) and The Cancer Genome Atlas (TCGA) datasets showed that WSTF was up-regulated in GBM tissues. Moreover, WSTF was also increased in the GBM cells. pcDNA-mediated over-expression of WSTF contributed to cell proliferation and invasion of GB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(26 reference statements)
1
1
0
Order By: Relevance
“…Survival analysis suggested that overexpression of BAZ1B was associated with poor prognosis in most tumors, especially in KIRC, LGG, LUAD, and MESO. This is consistent with the conclusion that Meng, et al [9] in studying LUAD and Yang, et al [38] in studying GBM, which both conclude that BAZ1B as an oncoprotein accelerates the proliferation and invasion of cancer cells among cancer patients.…”
Section: The Williams Syndrome Transcription Factor (Wstf)supporting
confidence: 90%
“…Survival analysis suggested that overexpression of BAZ1B was associated with poor prognosis in most tumors, especially in KIRC, LGG, LUAD, and MESO. This is consistent with the conclusion that Meng, et al [9] in studying LUAD and Yang, et al [38] in studying GBM, which both conclude that BAZ1B as an oncoprotein accelerates the proliferation and invasion of cancer cells among cancer patients.…”
Section: The Williams Syndrome Transcription Factor (Wstf)supporting
confidence: 90%
“…For instance, overexpression of NCAPG2 can regulate the activation of Wnt/β-catenin pathway to promote proliferation, migration, and invasion of GBM cells, and knockdown of NCAPG2 inhibited tumorigenesis of GBM in vivo ( 33 ). Also, the high expression of BAZ1B can also increase proliferation, migration, invasion, and inhibition of apoptosis in GBM cells ( 34 ). In our study, the NCAPG2 and BAZ1B genes were positively related to NUP205 and have been reported as oncogenes for glioma.…”
Section: Discussionmentioning
confidence: 99%